Treatment of piggery wastewater in UASB reactor and water-hyacinth pond - Nhu, Dang Xuyen; Son, Pham Huong; Cuong, Nguyen Phu; Lan, Nguyen Thi; Dinh, Duong Hong (Academia Journal of Biology, 2014)
Treatment of piggery wastewater in UASB reactor and water-hyacinth pond